Farmers' Resilience to The Impact of Climate Change in Teniga Village, Tanjung District, North Lombok - Anandytia, Hapidi; Sulistiyono , Heri; Markum (Jurnal Biologi Tropis, 2025)
Climate change has disrupted agricultural systems, especially in rural areas that depend on weather stability for food production. This study aims to analyze farmers’ resilience to climate change impacts in Teniga Village, Tanjung District, North Lombok Regency. A descriptive method combining qualitative and quantitative approaches was applied to 86 respondents selected purposively. Data were collected through questionnaires, observations, and documentation, then analyzed using descriptive statistics with Microsoft Excel and SPSS. The findings show that the overall resilience level of farmers is moderate, with an average score of 78,78, while the economic (18,08), social (20,72), and institutional (19,12) and disaster aspect (20,98) dimensions are categorized as low. Only the disaster resilience aspect showed moderate adaptation. These results indicate that although farmers have begun implementing adaptive actions such as crop diversification and water-saving practices, their capacity remains limited due to weak institutional support, restricted access to capital, and low community participation. Therefore, strengthening economic empowerment, institutional coordination, and community-based disaster management is essential to improve adaptive capacity and ensure the sustainability of local livelihoods amid changing climatic conditions.